Postnatal development of renal function in preterm and term neonates - Mannan, MA; Shahidulla, M; Salam, F; Alam, MS; Hossain, MA; Hossain, M (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):103-108 The abstract of this article is available on the PubMed website